Jurnal Review: Pengaruh Perbedaan Jenis Sampah Organik Terhadap Pertumbuhan Larva Bsf (Black Soldier Fly) dan Kecepatan Penguraian Sampah Organik - Restu Hikmah Ayu Murti; RATNA ENDAH DWI PUSPITASARI (Prosiding ESEC, 2023)
Nowadays, waste production in Indonesia is increasing, one of which is organic waste. The utilization of BSF (Black Slodier Fly) larvae as an organic waste reducer is an alternative to reducing waste in Indonesia. This journal uses a qualitative descriptive method with a type of literature study (research study), namely collecting information through scientific articles related to the utilization of BSF larvae as organic waste reducers. This study aims to determine the effect of different types of organic waste reduced by BSF larvae on larval growth and organic waste reduction speed. BSF larvae can reduce various types of organic waste such as fruit waste, vegetable waste, animal meat, and even decomposing waste. The humidity and temperature of the larval growth medium is one of the factors that influence the speed of the organic waste reduction process by BSF larvae.